Burnout, satisfaction and compassion fatigue: relationship with quality of care and patient safety - Ana Claudia Alcântara Garzin; Carla Maria Maluf Ferrari; Giovana Caldas Pereira; Kawany de Oliveira Rodrigues Duarte; Samara Gomes Rodrigues; Ivonete Sanches Giacometti Kowalski (O Mundo da Saúde, 2024)
Nurses who work in hospital care deal with physical and emotional pain, highly complex situations, exposure to suffering, fear, stress and anxiety, which favors the development of compassion fatigue, which is considered a form of suffering resulting from work activity. and can compromise the health and well-being of nurses, as well as patient safety. The objective was to relate compassion fatigue with aspects of the quality of healthcare and patient safety. This was an exploratory, quantitative, correlational study, carried out between May and June 2021. Data collection took place through an online questionnaire after approval from the Research Ethics Committee and consent from the participants. The sample consisted of 410 nurses who worked in three private hospitals in São Paulo; 319 (78%) were female, 212 (51.71%) had worked in hospitals for 4 to 10 years. Positive correlations were obtained between high rates in the compassion fatigue and burnout dimension of the ProQol-Br questionnaire and aspects related to quality of care and patient safety (p<0.001). The nurses agreed that due to work overload and mental exhaustion, they failed to fully comply with quality and patient safety protocols, which could increase the occurrence of adverse events. The relevance of developing strategies to improve work overload was highlighted, through the adequacy of human resources, satisfaction and professional recognition, in order to minimize the occurrence of compassion fatigue and have a positive impact on the quality of care and patient safety.